Innovating out of the fishmeal trap: The role of insect-based fish feed in consumers' preferences for fish attributes. Issue 10 (7th August 2018) - Ankamah-Yeboah, Isaac; Jacobsen, Jette Bredahl; Olsen, Søren Bøye
Abstract : Purpose: The purpose of this paper is to examine the potential market impacts of the use of insect-based protein for fish feed as an innovative approach out of the fish-meal trap. Design/methodology/approach: An online questionnaire was used to elicit information on fish consumption choices among 610 German consumers using a discrete choice experiment. Mixed logit and latent class logit models were used to model consumers' preference heterogeneity. Findings: Results show that consumers' preferences for fish attributes such as filets, freshness, ecolabelling and domestic production are heterogeneous and important in consumption choices. The minor share of the respondents is sensitive, while the remaining is indifferent regarding the use of insect based protein as feed in trout production. For this sensitive segment, consumption would be expected to be reduced unless the price is reduced or other attributes such as convenience aspects are improved. Research limitations/implications: The implication is that firms can substitute without a significant impact on the market demand given that the majority of consumers are indifferent regarding feed sources for trout production. As a result, it provides an innovative way to ensure sustainable use of resources and reduces the threat of fish meal trap while reducing pressure on the already over-exploited marine life. Originality/value: The results provide first insights into the market impact of using insects in the animal protein value chain. It is important especially with Europe's recent lift of the ban on using insect-based protein in the animal food industry.